Restrição hídrica e dietas sobre o comportamento ingestivo e respostas termorreguladoras em ovinos - Oliveira, Bruna Yasnaia de Souza (2014)
The objective of this study was to evaluate the effect of water restriction and low diets and high energy in thermoregulatory responses and feeding behavior of crossbred sheep of St. Agnes. 40 animals were used, not castrated, with average body weight of 18.85 +2.80 kg and approximately five months old, kept in individual stalls. The experimental diets were composed of Tifton 85 hay (Cynodon spp.) And concentrate (corn and soybeans) in a forage: concentrate ratio 3: 7 (highenergy diet) and 7: 3 (low-energy diet). Water was provided ad libitum and restricted in 50% of the daily need. The experimental design was completely randomized in a 2x2 factorial (two energy levels and soil water availability), with 10 repetitions for each factor. Data were analyzed by analysis of variance procedures. There was no interaction (P> 0.05) between dietary energy content and the availability of water, according to the analysis of variance, to feeding time, idling time. There was no interaction effect (P> 0.05) between the type of diet and the availability of water, according to the analysis of variance for the variables HR, TR and TS. There was an interaction effect (P <0.05) between the factors of dietary energy content and availability of water for the FR variable. There was no interaction effect (P> 0.05) between the factors of dietary energy content and availability of water, subject to the weight of organs and viscera.The dry matter intake was unchanged in water restriction interaction and dietary energy, and the development of organs and viscera, showing that the animals did not suffer water stress.